Banks’ Non-Interest Income and Systematic Risk: A Case of Nepalese Commercial Banks - Kandel, Sudha; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2024)
The study examines the determinants of non-interest income and systematic risk of Nepalese commercial banks. Non-interest income and systematic risk are selected as the dependent variables. The selected independent variables are nonperforming loan ratio, equity to total asset ratio, return on assets, net interest margin, bank size, operating efficiency and liquidity ratio. The study is based on secondary data of 27 commercial banks with 162 observations for the period from 2013/14 to 2018/19. The data are collected from the publications and websites of Nepal Rastra Bank and Ministry of Finance and annual reports of the selected commercial banks. The regression models are estimated to test the significance and importance of different variables on non-interest income and systematic risk of Nepalese commercial banks.The study showed that non-performing loan and net interest margin have a negative impact on non-interest income. It indicates that increase in non-performing loan and net interest margin leads to decrease in non-interest income. Likewise, equity to total asset ratio and return on assets have a positive impact on non-interest income. It implies that increase in equity to total asset ratio and return on assets leads to increase in non-interest income. Likewise, non-performing loan, operating efficiency, bank size and liquidity have a negative impact on systematic risk. It indicates that increase in non-performing loan, operating efficiency, bank size and liquidity leads to decrease in systematic risk.